2008
DOI: 10.1189/jlb.1107756
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the inflammatory subset of monocytes to sites of ischemia induces angiogenesis in a monocyte chemoattractant protein-1-dependent fashion

Abstract: There is accumulating evidence that delivery of bone marrow cells to sites of ischemia by direct local injection or mobilization into the blood can stimulate angiogenesis. This has stimulated tremendous interest in the translational potential of angiogenic cell population(s) in the bone marrow to mediate therapeutic angiogenesis. However, the mechanisms by which these cells stimulate angiogenesis are unclear. Herein, we show that the inflammatory subset of monocytes is selectively mobilized into blood after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 42 publications
9
91
0
Order By: Relevance
“…We found that, compared with wild-type animals, the vasculature within fracture callus in Ccr2-/-mice had a reduced surface area for nutrient exchange. This observation is consistent with other reports demonstrating that impaired macrophage recruitment in Ccr2-/-mice leads to a reduction in tissue vascular endothelial growth factor (VEGF) levels and a delay in capillary formation (Capoccia et al, 2008;Ochoa et al, 2007). Macrophages are key effectors of angiogenesis that contribute to tumor angiogenesis in several carcinomas (Mazibrada et al, 2008;Ohta et al, 2002), and tumor-associated macrophages have been shown to express VEGF (Gonzalez et al, 2007).…”
Section: Role Of Ccr2 and Macrophages During Early Fracture Healingsupporting
confidence: 81%
“…We found that, compared with wild-type animals, the vasculature within fracture callus in Ccr2-/-mice had a reduced surface area for nutrient exchange. This observation is consistent with other reports demonstrating that impaired macrophage recruitment in Ccr2-/-mice leads to a reduction in tissue vascular endothelial growth factor (VEGF) levels and a delay in capillary formation (Capoccia et al, 2008;Ochoa et al, 2007). Macrophages are key effectors of angiogenesis that contribute to tumor angiogenesis in several carcinomas (Mazibrada et al, 2008;Ohta et al, 2002), and tumor-associated macrophages have been shown to express VEGF (Gonzalez et al, 2007).…”
Section: Role Of Ccr2 and Macrophages During Early Fracture Healingsupporting
confidence: 81%
“…By binding to their specific Gprotein-coupled receptors, chemokines induce cell-specific migration and activation of immune cells (Glabinski et al, 1996;Hulkower et al, 1993;Lahrtz et al, 1998;Miller and Meucci, 1999). Monocyte chemoattractant protein-1 (MCP1; officially known as C-C motif chemokine 2, CCL2) is one of the most highly and transiently expressed chemokines in many central nervous system (CNS) injuries, including ischemia, hemorrhage and excitotoxic injury (Capoccia et al, 2008;Dimitrijevic et al, 2006;Frangogiannis et al, 2007;Hanisch, 2002;Kim et al, 2008;Morimoto et al, 2008;Sheehan et al, 2007;Yan et al, 2007). The rodent MCP1 differs from the human protein at the C-terminus, with the rodent protein having a longer highly glycosylated Cterminus.…”
Section: Introductionmentioning
confidence: 99%
“…37 Also, Nef is a migratory stimulus for monocytes 38 and induces the release of infl ammatory molecules. 39 Capoccia and colleagues 40 proposed a model in which Nef induces early recruitment of infl ammatory monocytes, which in turn induce a secondary wave of monocytes followed by angiogenesis.…”
Section: Nef Is Mutated In the Lung Of A Patient With Hrpahmentioning
confidence: 99%